Exploring an agency-communion model of identity transformation in recovery from substance misuse. (4th May 2019) - Rowlands, David; Youngs, Donna; Canter, David
ABSTRACT: Background: Narrative research shows that identity change is key to recovery from substance misuse. Theories have focused on either personal or social factors in this process. A framework encompassing Agency and Communion has been useful in understanding narratives in similar populations. Objectives: The study proposes that substance misuse and recovery can be understood from an Agency-Communion perspective. Method: The Life As A Film Task (LAAF) and repertory grids were used to explore Agency and Communion in a sample of 32 participants. Results: Smallest Space Analysis of LAAF items revealed four different narratives according to themes of Agency and Communion. Case examples indicated that Agency and Communion predicted a recovery identity, and the absence of Agency and Communion predicted substance misuse. Analysis of repertory grids showed fixed low Agency/Communion construct systems in cases of substance misuse and transformed high Agency/Communion construct systems in cases of recovery. Transformation from a low Agency/Communion substance-using identity toward a high Agency/Communion recovery identity was highlighted. Conclusions: These preliminary findings illustrate the role of Agency and Communion processes in identity-transforming recovery from substance misuse.